2013
DOI: 10.1177/0268355513494375
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of circulating markers in primary chronic venous insufficiency

Abstract: Whilst a number of studies have examined biomarkers associated with primary chronic venous insufficiency, further studies are required using improved and standardized approaches on larger populations. Biomarker research may increase pathogenic knowledge and result in opportunities to decrease chronic venous insufficiency burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
(147 reference statements)
0
10
0
Order By: Relevance
“…There is no clear consensus on which circulating biomarkers are associated with CVD. 13 Numerous hypotheses have been proposed to explain the mechanisms by which patients with venous hypertension and early stage venous disease progress to late stage venous disease. Major hypotheses that have been proposed include the pericapillary fibrin cuff theory, the growth factor trap hypothesis and the white cell trapping hypothesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no clear consensus on which circulating biomarkers are associated with CVD. 13 Numerous hypotheses have been proposed to explain the mechanisms by which patients with venous hypertension and early stage venous disease progress to late stage venous disease. Major hypotheses that have been proposed include the pericapillary fibrin cuff theory, the growth factor trap hypothesis and the white cell trapping hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Limitations of the previous studies include small sample sizes (case subject range: 25-100), absence of examination of control populations by venous duplex ultrasonography and lack of adjustment for other risk factors. 13 The previous studies have also not focused on markers of more severe CVD and differ in their definitions of hyperhomocysteinemia. 24,25 In order to address these limitations, we sought to undertake a study to examine the association of circulating homocysteine with the skin complications of primary CVD with adjustment for potential confounding risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid shear stress causes venous distension and causes increase in cellular responses. These changes trigger inflammatory mediators [21][22][23] . Karahan et al 24 evaluated the relationship between inflammatory markers and clinical severity of chronic venous insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent systematic review of the literature showed that circulating estradiol, homocysteine, and vascular endothelial growth factor were the markers most consistently associated with primary chronic venous insufficiency. 59 Another limitation is that the control group answered only the BDI score without a clinical assessment from a psychiatrist. In the DD group, some patients were already on antidepressant therapy, and thus this may have influenced their laboratory biomarkers.…”
Section: Discussionmentioning
confidence: 99%